2012
DOI: 10.1007/s13691-012-0047-9
|View full text |Cite
|
Sign up to set email alerts
|

Successful management of chemotherapy in a stage IV ovarian cancer patient with chronic renal failure

Abstract: Because the number of hemodialysis patients is increasing, chemotherapy will need to be performed on more of these patients in the future. Carboplatin is metabolized by the kidneys and excreted in the urine, so delayed excretion caused by renal dysfunction can lead to severe adverse effects. Here, we report on the successful and safe performance of chemotherapy in a hemodialysis patient with stage IV ovarian cancer, based on alteration of the dialysis time and pharmacokinetic monitoring. A 60-year-old woman on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…This is a report on the feasibility of the use of paclitaxel and carboplatin in a Chinese HD patient. The doses of paclitaxel and carboplatin were similar to those used in a previous report from Japan 8 . Paclitaxel is metabolized mainly in the liver and secreted into bile.…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…This is a report on the feasibility of the use of paclitaxel and carboplatin in a Chinese HD patient. The doses of paclitaxel and carboplatin were similar to those used in a previous report from Japan 8 . Paclitaxel is metabolized mainly in the liver and secreted into bile.…”
Section: Discussionsupporting
confidence: 54%
“…It seems that there is no clear correlation between the dose of free platinum and bone marrow suppression. In addition, Kaku et al 8 reported that by changing the interval between the infusion and HD, the AUC can be reduced, thereby reducing blood toxicity after carboplatin chemotherapy. Takeda also confirmed this view 19 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations